GAMBARAN KESIAPSIAGAAN RUMAH SAKIT IBU DAN ANAK (RSIA) AL ISLAM BANDUNG DALAM MENGHADAPI KONDISI DARURAT ATAU BENCANA - Lola Sugiarni; Arif Susanto (LPPM Akper Kebonjati, 2023)
Emergency or disaster preparedness is one aspect of assessing the quality of a hospital (RS). Hospitals that are oriented towards patient safety will fulfill policies and procure disaster management facilities and infrastructure in accordance with established standards. Al Islam Bandung Mother and Child Hospital (RSIA) is located in a densely populated area of 16,227 people. This makes RSIA Al Islam Bandung vulnerable to disaster events. In ensuring that the hospital can deal with emergencies or disasters, it is necessary to analyze the description of hospital preparedness in handling emergencies or disasters. This descriptive qualitative research uses interviews, observation, and document review methods in collecting research data. The number of informants was 6 (six) people. The results showed that the hospital's preparedness in dealing with emergencies or disasters was in accordance with the Minister of Health Regulation Number 66 of 2016 and the Technical Guidelines for Emergency Preparedness of the Ministry of Health in 2020. RSIA AL Islam Bandung has fulfilled 5 (five) steps of preparedness for emergency or disaster conditions with an achievement of 79%. This figure is based on the results of the fulfillment calculation according to the list of document reviews and field observations. RSIA AL Islam Bandung is expected to evaluate the disaster management program that has been made, then optimize it by involving all related teams and supervised by the Hospital Director.